The effect of workload and work ambiguity on burnout with work stress as a mediation variable - Suganda Putri, Gita; Lukito, Hendra; Amali Rivai, Harif (Jurnal Mantik, 2024)
The purpose of this research is to analyze the factors which cause employees to burnout in working, which include workload and work ambiguity on burnout with work stress that employees feel as a mediation variable. Burnout is an important thing that must be considered by company management in managing company resources or employees. The populations in this study are Non Civil Servant Nurses dr. Reksodiwiryo Army Hospital, Padang CityWest Sumatera with a sample of 90 nursees. The analytical method used descriptive statistical analysis and factor description analysis using SmartPLS 4.0. The result of this study shows that workload has a positive and significant effect on work stress; work ambiguity has a negative and significant effect on work stress; workload, work ambiguity, and work stress have a significant impact on burnout; work stress as a mediating variable has an effect on the workload on burnout and work ambiguity on burnout